The Role of Brand Image in Mediating the Influence of Green Marketing on the Decision to Purchase Galloon Packaged Mineral Water from the Aqua Brand - PARAMANANDA, Nyoman; IDAWATI, Ida Ayu Agung (International Journal of Environmental, Sustainability, and Social Science, 2023)
The decline in the position of the Aqua brand mineral water is reflected in the decline in the Top Brand index ranking. It indicates a change in consumer purchasing decisions regarding Aqua brand gallon bottled mineral water due to the issue of BPA content, which is unhealthy or environmentally friendly. This research aims to determine the role of brand image in mediating the influence of green marketing on the decision to purchase gallon bottled mineral water from the Aqua brand. The method for determining the sample in the research is non-probability sampling with a purposive sampling technique. The population in this study were all consumers of Aqua brand gallon bottled mineral water. The data analysis technique uses path analysis. The research results show that green marketing has a positive and significant effect on purchasing decisions, green marketing has a positive and significant effect on brand image, brand image has a positive and significant effect on purchasing decisions, and green marketing has an indirect effect on purchasing decisions through brand image.